2016
DOI: 10.18632/oncotarget.10074
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the neonatal Fc receptor expression in non-small cell lung cancer tissue is associated with a poor prognosis

Abstract: Lung cancer is the leading cause of cancer-related death worldwide. Although the recommended tumor, node and metastasis (TNM) classification and stage determination are important to select therapeutic options for patients with non-small cell lung carcinoma (NSCLC), additional molecular markers are required to indicate the prognosis, in particular within a specific stage, and help with the management of patients.Because neonatal Fc receptor (FcRn) has recently been involved in colon cancer immunosurveillance, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
45
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 42 publications
7
45
0
3
Order By: Relevance
“…Consistent with recent analyses of the expression of this receptor in lung cancer [13], the majority of tumor cell lines have very low to undetectable levels of FcRn. Importantly, we demonstrate that the growth of tumors in xenograft models is significantly higher for cells with lower, or knocked down, expression of FcRn.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with recent analyses of the expression of this receptor in lung cancer [13], the majority of tumor cell lines have very low to undetectable levels of FcRn. Importantly, we demonstrate that the growth of tumors in xenograft models is significantly higher for cells with lower, or knocked down, expression of FcRn.…”
Section: Introductionsupporting
confidence: 85%
“…Further, the correlation of FcRn expression levels at the tumor site with favorable prognosis has been proposed to relate to the function of this receptor in hematopoietic cells [13]. However, in addition to the immunological activity of FcRn involving IgG interactions and antigen presentation [2527], our studies demonstrate that the levels of this receptor within the tumor cells themselves modulate cancerous growth by regulating albumin accumulation.…”
Section: Discussionmentioning
confidence: 71%
“…The density of FcRn-expressed DCs was correlated with CD8 + T-cell number and predicted improved prognosis in human colorectal carcinoma. Second, we reported FcRn mRNA and protein levels in both lung cancerous tissue and non-cancerous tissue associated with favorable prognosis in non-small cell lung cancer ( 13 ). Third, studies involving neoplastic cells expressing different levels of FcRn showed that FcRn-mediated recycling of albumin reduced tumor cell growth and proliferation ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…FcRn also plays an important role in adaptive immunity. (12,(20)(21)(22)(23)(24) Studies in dendritic cells have established that FcRn is necessary for trafficking antigen-antibody complexes for degradation as well as presentation on MHCII. (10,20,25,26) Furthermore, studies have shown that when FcRn is absent, dendritic cells cannot present antigen for antigen presentation.…”
Section: Introductionmentioning
confidence: 99%